Comparison of early onset sepsis and community-acquired late onset sepsis in infants less than 3 months of age. Issue 1 (December 2016) - Bulkowstein, Shlomi; Ben-Shimol, Shalom; Givon-Lavi, Noga; Melamed, Rimma; Shany, Eilon; Greenberg, David
Abstract Background We compared demographic and clinical characteristics of early-onset sepsis (EOS) and community-acquired late onset sepsis (CA-LOS) in infants. Methods Our medical center is the sole hospital in southern-Israel, enabling incidence calculations. EOS (<7 days) and CA-LOS (7–90 days) episodes recorded between 2007 and 2013 were reviewed. Univariate and multivariate analyses were performed. Results 70 EOS and 114 CA-LOS episodes were recorded. The respective mean ± SD annual rates per 1, 000 live-births were 0.66 ± 0.16 and 1.03 ± 0.23. Prematurity (42.9 % vs. 17.0 %), premature rupture of membranes (PROM; 22.9 % vs. 1.9 %), leukopenia (29.0 % vs. 11.6 %), thrombocytopenia (44.9 % vs. 14.3 %) andStreptococcus agalactiae infections (22.7 % vs. 8.1 %) were more common in EOS. Fever (25.4 % vs. 79.1 %) andStreptococcus pneumoniae infections (1.3 % vs. 12.9 %) were less common in EOS. In both groups, Gram-negative bacteria predominated ( 60 %). Longer hospitalization duration (23.3 ± 25.1 vs. 10.3 ± 8.6 days) and higher case fatality rate (20.0 % vs. 5.3 %) were noted in EOS. Antibiotic resistance rates to empiric EOS and CA-LOS treatments were 0.0 % and 1.2 %, respectively. In multivariate analysis, adjusting for prematurity and ethnicity, PROM, central line, low Apgar-score, low birth-weight, ventilation support and non-vaginal delivery were risk factors for EOS. Normal temperature, thrombocytopenia and leukopenia characterized EOS. Conclusion EOS and CA-LOS rates were low in Jewish compared with Bedouin infants. EOS was characterized by higher rates of perinatal risk factors, S. agalactiae infections, normal temperature, thrombocytopenia, leukopenia and mortality, while fever andS. pneumoniae infections were common in CA-LOS. Current initial antibiotic regimens seem adequate, considering the susceptibility patterns of the isolated pathogens